2020
DOI: 10.1016/j.arbres.2020.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Video-Assisted Thoracic Surgery Group: Method, Auditing, and Initial Results From a National Prospective Cohort of Patients Receiving Anatomical Lung Resections

Abstract: Introduction: Our study sought to know the current implementation of video-assisted thoracoscopic surgery (VATS) for anatomical lung resections in Spain. We present our initial results and describe the auditing systems developed by the Spanish VATS Group (GEVATS). Methods: We conducted a prospective multicentre cohort study that included patients receiving anatomical lung resections between 12/20/2016 and 03/20/2018. The main quality controls consisted of determining the recruitment rate of each centre and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 26 publications
0
3
0
5
Order By: Relevance
“…Ello puede ocasionar un sesgo de selección relevante. Sin embargo, cabe destacar que se excluyeron los pacientes procedentes de centros con bajas tasas de reclutamiento (la mediana de reclutamiento global fue del 99% (p25-p75: 76-100%), y se llevó a cabo una auditoría interna de la calidad de los datos (el grado de concordancia fue del 98%) 15 . -Los niveles de albúmina en sangre, que en varios estudios ha demostrado un impacto pronóstico en pacientes sometidos a cirugía, no pudo ser analizado debido al elevado porcentaje de pacientes sin ese dato.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ello puede ocasionar un sesgo de selección relevante. Sin embargo, cabe destacar que se excluyeron los pacientes procedentes de centros con bajas tasas de reclutamiento (la mediana de reclutamiento global fue del 99% (p25-p75: 76-100%), y se llevó a cabo una auditoría interna de la calidad de los datos (el grado de concordancia fue del 98%) 15 . -Los niveles de albúmina en sangre, que en varios estudios ha demostrado un impacto pronóstico en pacientes sometidos a cirugía, no pudo ser analizado debido al elevado porcentaje de pacientes sin ese dato.…”
Section: Discussionunclassified
“…Por otro lado, conocer de forma objetiva el riesgo quirúrgico es especialmente interesante en el contexto actual, en el que se plantean tratamientos alternativos a la cirugía para determinados tipos de pacientes. El objetivo de nuestro trabajo es desarrollar un modelo predictor de morbimortalidad posquirúrgica en pacientes sometidos a una resección pulmonar anatómica a partir de la base de datos del Grupo Espa ñol de Cirugía Torácica Videoasistida (GEVATS) 15 .…”
unclassified
“…Major video-assisted thoracic surgery (VATS) is fully developed in Spain, Currently, more than half of all anatomical resection in the country are performed via VATS (15).…”
Section: Technological Developmentmentioning
confidence: 99%
“…Video-assisted thoracoscopic surgery (VATS) is the current procedure of choice for most resections in this setting. A recent nationwide cohort study conducted in Spain reported that over 50% of recent anatomic lung resections had been performed by VATS[ 6 ]. The main advantages of VATS compared with open surgery are decreased postoperative pain, fewer postoperative complications, and in some cases even, better oncological outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in VATS techniques and the design of specific surgical material have led to a progressive reduction in the number of incisions required. Most thoracic surgeons now use between one and three incisions and describe similar oncological results[ 6 , 7 ]. Subxiphoid VATS is another minimally invasive technique associated with good outcomes when performed by teams with extensive experience in VATS; it has been linked to a lower incidence of postoperative neuropathic pain[ 8 ].…”
Section: Introductionmentioning
confidence: 99%